2022
DOI: 10.3389/fpsyg.2022.849847
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Regional Homogeneity of Resting-State fMRI Between the Early-Onset and Late-Onset Recurrent Depression in Adults

Abstract: BackgroundNeurobiological mechanisms underlying the recurrence of major depressive disorder (MDD) at different ages are unclear, and this study used the regional homogeneity (ReHo) index to compare whether there are differences between early onset recurrent depression (EORD) and late onset recurrent depression (LORD).MethodsEighteen EORD patients, 18 LORD patients, 18 young healthy controls (HCs), and 18 older HCs were included in the rs-fMRI scans. ReHo observational metrics were used for image analysis and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Emotions can be transmitted to the insula through interconnections with the amygdala and orbitofrontal cortex to receive and integrate positive and negative endoceptive information [ 49 , 50 ]. Previous studies have found SN abnormalities in patients with RDE [ 35 , 51 ]. The improvement in clinical symptoms in patients with MDD may be related to escitalopram modulation of the ReHo of the insula [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Emotions can be transmitted to the insula through interconnections with the amygdala and orbitofrontal cortex to receive and integrate positive and negative endoceptive information [ 49 , 50 ]. Previous studies have found SN abnormalities in patients with RDE [ 35 , 51 ]. The improvement in clinical symptoms in patients with MDD may be related to escitalopram modulation of the ReHo of the insula [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experienced psychiatrists evaluated patients with RDE according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria. The patients were required to meet the following inclusion criteria [ 23 , 35 ]: (1) age 18–60 years, (2) right-handedness, (3) a 17-item Hamilton Rating Scale for Depression (HAMD-17) score >17, and (4) the RDE group having a previous history of MDD that was remitted with antidepressants or other therapies and was now relapsing, and they had not been taking antidepressants for at least 4 weeks before enrollment. Meanwhile, we used advertising recruitment to include a total of 43 healthy controls (HCs) who were relatively matched to the RDE group in terms of sex and age.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations